An integration action research (IAR) on engaging employees to improve work satisfaction - Lagman, Mia Marie G. (Animo Repository, 2021)
When expectations on the working conditions are not met by a company, the employees feel less content towards their job. As more and more employees feel the same, it becomes inevitable for them not to talk about it. Negativity surrounds the work environment that eventually leads to unfavorable behavior, strained relationships, low performance, loss of motivation and potential resignations. An action research was applied to a unit of this company where the subjects volunteered to be collaborators in improving their level of work satisfaction. Critical realism approach was adopted to seek the factors contributing to the issue while first and second-person tools were used to validate the concern. The insider who was also part of the unit strategized to pursue a high-level sponsor from the management to reduce biases and confirm workability of the solutions. The sponsor became aware of the situation of the unit and even initiated supplemental programs. After two cycles of research, the solutions of creating a work prioritization matrix, having a department and townhall meeting, and devising a leadership feedback form and employee recognition program improved the level of contentment of the employees as demonstrated by the force field analysis. Work satisfaction may be too conventional for some companies due to its unattainability, but the basics of it should not be forgotten. Satisfied employees are still a must for every company. A general framework was established to improve satisfaction of one’s own team. It is the responsibility and accountability of every leader to look out for his team’s well-being to create a humane and harmonious workplace.